Chapter «La Basilica di S. Miniato al Monte sta a noi se si vuole». Il ritorno dei monaci olivetani nel 1924 - Donghi, Roberto (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
The paper retraces the negotiations undertaken by the Olivetan monks at the beginning of the 20th century for their return to the ancient abbey of San Miniato al Monte, which they had been forced to abandon in 1552 for the construction of the ramparts to defend the city. Given its location, other religious orders wanted to settle there, such as the Vallombrosans of Santa Trinita and the Cassinesi of the Florentine Abbey, but the Olivetans claimed their rights. So on 11th July 1924 the visiting abbot Benedetto Benedetti signed the deed of delivery to his regular family. The official entrance, disclosed by the town press, took place on Sunday 26 October 1924, and the resumption of the monastic life the following year, under the guidance of Don Gaetano Romagnoli, the first abbot of the restored Olivetan community.